2018
DOI: 10.1007/jhep01(2018)108
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Higgs searches: flavour matters

Abstract: We point out that the stringent lower bounds on the masses of additional electrically neutral and charged Higgs bosons crucially depend on the flavour structure of their Yukawa interactions. We show that these bounds can easily be evaded by the introduction of flavour-changing neutral currents in the Higgs sector. As an illustration, we study the phenomenology of a two Higgs doublet model with a Yukawa texture singling out the third family of quarks and leptons. We combine constraints from low-energy flavour p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…Following the discussions made explicitly in refs. [46,85,144], which are sufficient for the current purpose, we have found that all these experimental bounds can be satisfied by the parameter regions allowed by the R D ( * ) and R K ( * ) anomalies. As a further nonzero ct needs to be introduced to X u 1 in order to provide a resolution to the muon g − 2 excess while complying with the tight constraints from the B-physics observables [136], we plan to perform a detailed study of the direct LHC constraints on the charged and neutral scalars at nonzero values of tt , tc and ct , as well as the neutrino Yukawa couplings in an upcoming paper.…”
Section: Numerical R K ( * ) Analysismentioning
confidence: 67%
“…Following the discussions made explicitly in refs. [46,85,144], which are sufficient for the current purpose, we have found that all these experimental bounds can be satisfied by the parameter regions allowed by the R D ( * ) and R K ( * ) anomalies. As a further nonzero ct needs to be introduced to X u 1 in order to provide a resolution to the muon g − 2 excess while complying with the tight constraints from the B-physics observables [136], we plan to perform a detailed study of the direct LHC constraints on the charged and neutral scalars at nonzero values of tt , tc and ct , as well as the neutrino Yukawa couplings in an upcoming paper.…”
Section: Numerical R K ( * ) Analysismentioning
confidence: 67%
“…For a recent discussion of flavour violation involving the top quark see Ref. [86]. Finally, H, A → γγ in our model is particularly interesting in light of the CMS excess at 95 GeV.…”
Section: Discussionmentioning
confidence: 86%
“…In our flavorful 2HDMs, 50% of the time the final state will be same-sign tops, in contrast to 2HDMs with natural flavor conservation that only produce opposite sign tops. Same-sign tops have been identified as important probes in a number of new physics scenarios, including RPV SUSY [56], 2HDMs [35,57,58], additional scalars [59,60], colored vectors [61], and effective field theories [62]. The cross section of same-sign tops in our scenario is shown in the left plot of In [55] searches for same-sign leptons are interpreted in a benchmark model in which same-sign tops are created by a neutral spin-1 mediator.…”
Section: Collider Signaturesmentioning
confidence: 89%
“…2HDMs with a right-handed top that is singled out by a symmetry have been discussed e.g. in [28,35]. Here we follow the second option and set the U (1) charges Q Φ = −Q Q 3 = +1, while leaving the right-handed top uncharged.…”
Section: Flavorful 2hdms With Up Sector Ckmmentioning
confidence: 99%
See 1 more Smart Citation